PERANCANGAN MEDIA PROMOSI COFFEE CORNER SEBAGAI UPAYA MENINGKATKAN BRAND LOYALTY - Abbas, Rifky Rafsanjani; Bahruddin, Muh; Riqqoh, Abdullah Khoir (Jurnal Art Nouveau, 2014)
Coffee Corner is the originator of coffeeshop outside Mall in Surabaya. Coffee Corner was established in 2007, which addressed at Jalan Arif Rahman Hakim, Surabaya. The name it is taken from the Coffee Corner interior layout that puts the bar in the corners of the room. The drinks Menu is provided here not only drinks coffee, but there are also tea, and fruit-flavored drinks like milkshakes taste of chocolate, strawberry, etc. In the development of this business, Coffee Corner is starting to get a lot of new competitors. Therefore, the Coffee Corner in need of a thorough media promotions can boost brand loyalty so that his customers did not switch to the new rivals.